Religionsunterricht oder Ethikunterricht? Entstehung des Religionsunterrichts - Rechtsentwicklung und heutige Rechtslage - politischer Entscheidungsbedarf - Kreß, Hartmut (Schriften zum Weltanschauungsrecht, 2022)
Denominational religious education in the Federal Republic of Germany is undergoing a deep structural crisis. It has been the subject of controversial discussions in educational and legal policy since as early as the 19th century. During the deliberations on the Weimar Constitution and subsequently on the Basic Law (Grundgesetz) of the Bonn Republic, religious education triggered serious disputes. Meanwhile, the legal problems pertaining to religious education have worsened across the federal states of Germany. The book emphasises the need for political reform. In the future, the existing religious education should be replaced by the subject of ethics/religious studies.